Penerapan Metode First In First Out (FIFO) Terhadap Penjualan Pada Cafe Titik Hitam Nalar Berbasis Android - Mohammad Fazrie; Parulian, Dudi; Bahtera Alam Wijaksono (STEKOM PRESS, 2024)
The business of selling coffee in the world is growing more easily and quickly with the provision of a place which is usually called a cafe or shop. One of them is the Titik Hitam Nalar cafe in Jakarta, but the ordering process with customers takes longer to wait for orders and customer payments that are not neatly arranged create conditions that’s are not conducive, resulting in continuous negative criticism. Therefore, an application is needed that helps employees work in every part, both in terms of ordering, manufacturing, and payments, using the FIFO algorithm which focuses on which services are prioritized first in order to reduce negative sentiment from customers. The Android-based application was created by involving every design phase, making it easier for customers and employees to provide a service facility that works well and is suitable for use.